NEVER ENDING STORIES TRANSFORMATION OF A PAPER STORAGE IN FORSÅKER - LINDBÄCK, IDA; JONSSON, ELLEN (My University, 2023)
The purpose of this thesis is to illustrate how building transformations using circular design principles can lower emissions and minimize resource extraction while also enabling more rich, functional and enjoyable environments. With a rapidly growing global population the pressure on nature and natural resources can be expected to further increase. The Swedish building sector already accounts for 40% of national greenhouse gas emissions and waste generation and 45% of our resource extraction. To avoid the worst-case climate scenarios, it is necessary to make a shift in the current linear system and explore new ways to design, build and live. This thesis will address these problems by showcasing how a transformation of an industrial building in Forsåker can help lower the environmental impact, revitalize a neglected neighbourhood and add new layers to the story and identity of the place. The project focus on designing out waste and extending the buildings life span by creating more adaptable spaces, utilizing reused and regenerative materials and designing new additions for future reuse. Furthermore, the program of this project strives to intensify the use of the building and promote more sustainable lifestyles within a circular economy, such as offering functions that support sharing goods, services and space. The carbon and resource savings made in this project are highlighted through a life cycle analysis. The result shows that the structure and climate shell of the existing building contains 10 960 tons materials and 1 390 tons embodied carbon, which is almost 3 times the embodied carbon and more than 30 times of the material mass compared to the new additions.
Keywords: Circularity – Transformation – Reuse